Personality traits and investors risk behaviour: moderating role of financial literacy / Muhammad Akhtar and Muhammad Umair Malik - Akhtar, Muhammad; Umair Malik, Muhammad (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
The aim of the study is to examine whether personality traits are associated with investors trading risk behaviour in stock markets. Furthermore, it establishes the association of financial literacy by employing the moderated multiple regression analysis. The findings reveal that personality traits have significant influence on investors risk behaviour while financial literacy modifies the basic relationships between personality traits and investors risk behaviour. The findings also conclude that behavioural impact was not only predetermined by individuals' genetic traits but also influenced by financial literacy. The current study provides valuable insights for investors and adamant grounds for future research. The two-fold role of individuals’ personality in case of gains and losses can be of interest for researchers in the future.